2021
DOI: 10.1186/s41984-021-00101-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus associated with occipital encephalocele: surgical management and clinical outcome

Abstract: Background Encephaloceles are cystic congenital malformations in which central nervous system (CNS) structures, in communication with cerebrospinal fluid (CSF) pathways, herniate through a defect in the cranium. Hydrocephalus occurs in 60–90% of patients with occipital encephaloceles. Objective Assessment of the surgical management of hydrocephalus associated with occipital encephalocele and its effect on the clinical outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 23 publications
2
21
1
1
Order By: Relevance
“…15,23,24 In general, ECs have a favorable prognosis with a mortality rate below 10%. 4,6,13,20 However, the presence of some predictors has been shown to worsen the prognosis 9,14 and affect the neurodevelopmental outcome. 2,6,11,12 Many studies have descriptively reported neurodevelopmental outcomes of patients with ECs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…15,23,24 In general, ECs have a favorable prognosis with a mortality rate below 10%. 4,6,13,20 However, the presence of some predictors has been shown to worsen the prognosis 9,14 and affect the neurodevelopmental outcome. 2,6,11,12 Many studies have descriptively reported neurodevelopmental outcomes of patients with ECs.…”
Section: Discussionmentioning
confidence: 99%
“…The general estimated rate of NDD in patients with EC has varied among several studies, with some authors 9,17,19,25 reporting overall rates between 16% and 31%. 6 However, other authors-for example, Lo et al, 2 Da Silva et al, 6 and Nagy and Saleh 20 -estimated the overall rate of NDD to be 52%, 60%, and 82.4%, respectively. Although 94 patients in the present cohort were able to have their NDD outcomes evaluated, the overall NDD rate was estimated to be 33%, which is slightly higher than the average estimated rate in the literature.…”
Section: Ndd In Patients With Ecsmentioning
confidence: 96%
See 3 more Smart Citations